Winter Tourism Product Development In Rovaniemi For Lapland Safaris - Joseph, Sunday; H. Ariyananda , Osmund (Rovaniemen ammattikorkeakoulu, 2010)
In our thesis, we integrated the different theories of tourism product development with the current practice of the several products/services offered in Lapland Safaris. The first part of our thesis was the theoretical analysis of the available studies done in tourism product development. We discovered four new approaches to tourism product development: Co-creation, Story-telling, Authenticity and Meaningful experience. We also used one of the results: Holistic tourism product co-creation, from integrated tourism development project (ITDP). The project initiators were from Rovaniemi University of Applied Sciences, University of Lapland and Lapland Centre of Expertise for the Experience Industry (LTO). The second part of our thesis was the qualitative analysis where we did an in-depth interview and observation of French tourist during and after their stay in Rovaniemi. Also, we did an in-depth interview of some Lapland Safari guides. In the end, we provided Lapland Safari with some development suggestions by applying the four new approaches to tourism product development, holistic tourism product co-creation and the results of our qualitative analysis to their existing products/services.